2022
DOI: 10.1039/d1nr07187d
|View full text |Cite
|
Sign up to set email alerts
|

Peptide functionalized DNA hydrogel enhances neuroblastoma cell growth and differentiation

Abstract: Designing programmable biomaterials that could act as extracellular matrix and permits functionalization is a current need for tissue engineering advancement. DNA based hydrogels are getting significant attention owing to their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Differentiation of the human neuroblastoma SH-SY5Y cells was performed as explained in the earlier studies. 42,43 Briefly, at day 0, when undifferentiated SH-SY5Y cells reached to 60-80% confluence, cells were trypsinized (0.25% trypsin), cell counting was done by hemocytometer, and 5 × 10 5 cells were seeded in a T-25 flask. The retinoic acid (RA) was added freshly in the differentiation media at (10 µM) final concentration.…”
Section: Differentiation Of Sh-sy5y Cells Into Neuronsmentioning
confidence: 99%
“…Differentiation of the human neuroblastoma SH-SY5Y cells was performed as explained in the earlier studies. 42,43 Briefly, at day 0, when undifferentiated SH-SY5Y cells reached to 60-80% confluence, cells were trypsinized (0.25% trypsin), cell counting was done by hemocytometer, and 5 × 10 5 cells were seeded in a T-25 flask. The retinoic acid (RA) was added freshly in the differentiation media at (10 µM) final concentration.…”
Section: Differentiation Of Sh-sy5y Cells Into Neuronsmentioning
confidence: 99%
“…By co-culturing both of these cells on this hydrogel, cell–cell communication was enhanced significantly, followed by the acceleration of PC12 differentiation with an increase in pseudopodia and formation of HUVECs’ tube-like structure. Hivare et al used a DNA based hydrogel that was coated on a glass and chemically conjugated with a synthetic IKVAV peptide [ 141 ]. They reported that this hydrogel triggered the enhanced differentiation of the neuronal movement of cytoskeleton and microtubules, and it prolonged neurite length, and modified endocytic mechanisms in neuroblastoma-stem cells, compared to the unmodified DNA hydrogel and controls.…”
Section: Biomedical Applications Of Peptide-based Hydrogelsmentioning
confidence: 99%
“…Peptides derived from proteins can become important in the selective regulation of biological systems such as cell adhesions, proliferations, and differentiations . Nonetheless, many short linear peptides have limitations in achieving sufficient bioactivity due to proteolytic degradations and rapid internalizations into the cytosol without sufficient stimulation of membrane surface receptors .…”
Section: Introductionmentioning
confidence: 99%